Evaluating Facilitator Training Effectiveness Using Kirkpatrick Model in Indonesian Legislative Institution - Sorayya, Hilalatus; Iqbal, Muhammad; Irawan, M. Ary (Program Studi Pendidikan Luar Sekolah, 2025)
This study aims at evaluating the facilitator capacity building training program at the Legislative Human Resources Competency Development Center of the Indonesian House of Representatives Secretariat General, using the Level 1 and 2 Kirkpatrick evaluation model. This descriptive quantitative research employed total sampling technique with 28 participants from 12 different functional positions and work units. The evaluation was conducted using questionnaires based on Kirkpatrick's evaluation model, focusing on Level 1 (Reaction) and Level 2 (Learning). Data were analyzed using descriptive statistics with scores classified into five categories ranging from